2006
DOI: 10.1097/01.mlg.0000231310.90344.44
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Culture and Antibiotic Use in Patients With Pharyngitis

Abstract: Most patients seen for pharyngitis were tested for GABHS, but pediatric patients were tested more frequently than adults. Patients who received a GAST were less likely to receive antibiotics. The rates experienced in our tertiary academic institution are higher than previously quoted for community practice. When antibiotics were prescribed, they were usually appropriate for the treatment of GABHS based on current recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, the overall 0.95% (414 of 43 860) rate of antibiotic prescribing for a negative RST result was very low compared with other documented prescribing rates for acute pharyngitis in the absence of strict adherence to clinical guidelines. 22,23 CONCLUSION Clinical support tools built into an EMR and practitioner staff training related to adhering to nationally established, clinical practice guidelines including the proper RST, strep culture sample collection, and proper antibiotic prescribing techniques appear to have resulted in high rates of appropriate management of acute pharyngitis. The strategies used here of appropriate testing for group A streptococcal pharyngitis and withholding antimicrobial therapy for patients with a negative RST result indicate highquality health care delivery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the overall 0.95% (414 of 43 860) rate of antibiotic prescribing for a negative RST result was very low compared with other documented prescribing rates for acute pharyngitis in the absence of strict adherence to clinical guidelines. 22,23 CONCLUSION Clinical support tools built into an EMR and practitioner staff training related to adhering to nationally established, clinical practice guidelines including the proper RST, strep culture sample collection, and proper antibiotic prescribing techniques appear to have resulted in high rates of appropriate management of acute pharyngitis. The strategies used here of appropriate testing for group A streptococcal pharyngitis and withholding antimicrobial therapy for patients with a negative RST result indicate highquality health care delivery.…”
Section: Discussionmentioning
confidence: 97%
“…However, the overall 0.95% (414 of 43 860) rate of antibiotic prescribing for a negative RST result was very low compared with other documented prescribing rates for acute pharyngitis in the absence of strict adherence to clinical guidelines. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…A number of bacteria cause pharyngitis and tonsillitis, but the overwhelming majority of cases are caused by group A Streptococcus (GAS). In children, this organism is estimated to be responsible for 15 to 36% of cases of sore throat, 9,18 whereas in adults it is reported to account for 5 to 15% of cases of pharyngitis. Overall, GAS account for 15 to 30% of pharyngitis regardless of age.…”
Section: Bacterialmentioning
confidence: 99%
“…In fact, it is the only commonly occurring organism for which antibiotic therapy is indicated. 18 It has been shown that even bacterial infections are often self-limited; therefore, treatment goals are essentially to avoid complications of the oropharyngeal infection. 1,12 Penicillin used to be the mainstay of antibiotic classes used for management of this organism, and there has yet to be a case of reported penicillin resistance in GAS.…”
Section: Medicalmentioning
confidence: 99%